Electrostriction devices and methods for assisted magnetic navigation - WERP PETER R; VISWANATHAN RAJU R; RITTER ROGERS C (2015)
An apparatus and method for interventional navigation within a subject's body is provided in which a medical device having at least one electrostrictive element is adapted to cause the distal end of the medical device to bend in a given direction for improving navigation. The medical device may further comprise at least one magnetically responsive element on the distal end, which may be oriented in the approximate direction of a magnetic field that is applied to the subject's body. At least one method for navigating a medical device though a subject's body is provided, by changing the direction of an applied magnetic field to align a magnetically responsive element on the distal end for orienting the distal end, and by applying a voltage to at least one electrostrictive element disposed in the distal portion of the device for causing the distal end to change orientation from that achieved by application of the magnetic field alone.